Pengukuran Earning Per Share Pada Jakarta Islamic Index 70 - Astutik, Dwi; Kusuma, Septian Yudha; Makom, Maharani Rona; Sudarman, Sudarman (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
Viewed from the fundamental aspect, in 2018-2019 there was a decrease in cash changes in JII70 shares (-1.42%), in 2020 it increased (2.09%), but in 2021 there was another decrease of -0.57%. The amount of investment has decreased (-0.04%), in 2020 it increased by 1.57% but in 2021 it will decrease again (-1.34%). Liquidity, which increased slightly from 2018-2019 (0.01%) and increased again in 2020 by 0.03% to 2021 by 0.11%. It is interesting to study that the development of the company's ability to provide earnings per share during the Covid-19 pandemic has a relatively positive value (especially in 2020-2021). Novelty: this testing technique uses multiple linear regression least suare based on research with a qualitative design. Purpose: to examine the effect of changes in cash, investment and liquidity on earnings per share. Method: the research design was carried out using a quantitative approach. The population was determined by companies registered on JII70 for 2018-2021 (70 companies). Based on the purposive sampling method, 36 companies were obtained for 4 (three) years (144 data studied). The test uses the least suare multiple linear regression technique. Results: cash changes have no effect on earnings per share, investment has a negative effect and liquidity has a positive and significant effect on earnings per share.